Kepemimpinan Raja Salomo: Keberhasilan Dan Keruntuhannya - Grecetinovitria Merliana Butar-butar; Friska Deniwaty Pasaribu; Yohana Hotmita Simbolon (LPPM - STT Kadesi Bogor, 2024)
This research reviews King Solomon's leadership journey, highlighting the peak of his success as well as the decline due to moral mistakes. Solomon, known for his wisdom and prosperity, ruled well but fell due to eroding morality. The library study method is used by exploring sources such as books, journal articles and historical documents. Solomon's leadership highlighted three main principles that are relevant in the modern context. First, the importance of a relationship with God as a source of wisdom. Second, service to others as the essence of true leadership. Third, wisdom in decision making and accountability for it. This study provides valuable lessons for today's leaders, underscoring the need for loyalty to moral values ​​for leadership.